2014
DOI: 10.1159/000368923
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Aging: Focus on Mitochondrial DNA Damage in Atherosclerosis - A Mini-Review

Abstract: Atherosclerosis is a complex disease which can be described as an excessive fibrofatty, proliferative, inflammatory response to damage to the artery wall involving several cell types such as smooth muscle cells, monocyte-derived macrophages, lymphocytes, dendritic cells and platelets. On the other hand, atherosclerosis is a typical age-related degenerative pathology, which is characterized by signs of cell senescence in the arterial wall including reduced cell proliferation, irreversible growth arrest and apop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 54 publications
1
19
0
1
Order By: Relevance
“…30 Aging may lead to atherosclerosis via increased levels of oxidative stress, DNA damage, mitochondrial dysfunction, and altered balance of cell proliferation and apoptosis. 31 …”
Section: Discussionmentioning
confidence: 99%
“…30 Aging may lead to atherosclerosis via increased levels of oxidative stress, DNA damage, mitochondrial dysfunction, and altered balance of cell proliferation and apoptosis. 31 …”
Section: Discussionmentioning
confidence: 99%
“…This process has been implicated in several human diseases including atherosclerosis and aging 13 . Studies from humans and animal models have confirmed that atherosclerosis and mtDNA damage increase exponentially with aging 46 , and mitoOS level correlates with atherosclerotic lesion progression during aging 5, 7 . We previously showed that excessive mitoOS in atherosclerotic lesional myeloid cells (macrophages) accelerated lesion development via enhanced inflammation and increased recruitment of monocytes in young Ldlr −/− mice 8 .…”
Section: Introductionmentioning
confidence: 94%
“…During atherosclerosis progression, blood vessels are bombarded by different types of stresses. For example, high blood tension, glucose, and oxidized LDL (oxLDL) cause human endothelial dysfunction via a variety of oxidative stresses . In addition, endothelial cells become more sensitive to oxidative stress induced endothelial dysfunction , indicating that aging represses the endogenous protective ability of endothelial cells under oxidative attack.…”
Section: Introductionmentioning
confidence: 99%